Evaluating Business Process Management Maturity Using the Business Process Orientation Maturity Model: Evidence from a Coffee MSME in Jember, Indonesia - Amalia, Karina Nine; Nugrahani, Tri Agustina (J-INTECH ( Journal of Information and Technology), 2026)
This study investigates the maturity level of Business Process Management (BPM) in three coffee micro and small enterprises (MSMEs) supported by the Integrated Business Service Center (PLUT) of Jember Regency—BC, PT. FAI, and PT. RKS. These enterprises have demonstrated potential as Go-Digital MSMEs, as indicated by their adoption of digital platforms such as social media, e-commerce, and point-of-sales systems, as well as their participation in digital business facilitation programs. However, current evaluations of their business development remain predominantly focused on financial growth, limiting a comprehensive understanding of their process performance and organizational readiness. This study applies the Business Process Orientation Maturity Model (BPOMM) to assess and compare BPM maturity across nine dimensions. Using a qualitative case study approach based on interviews, observations, and member checking, the findings reveal that all three MSMEs remain at Level 1 (ad hoc), indicating that their business processes are largely unstructured and lack systematic management. The comparative analysis further uncovers differences in organizational structure formalization, the use of key performance indicators (KPIs), the extent of business process documentation, and the level of digital system integration supporting operational processes. This study contributes by contextualizing BPM maturity assessment within digital MSMEs and providing empirically grounded insights into process-related gaps that hinder their readiness for scaling and global market expansion. The findings offer practical implications for improving BPM practices while also suggesting the need for adapting maturity models to better capture the characteristics of digitally transforming MSMEs.